Peningkatan Kapasitas Melalui Pelatihan Interaktif Penggunaan Aplikasi Digital QRIS Sebagai Alat Pembayaran Pada Desa Wisata Cemara Kulon - Dian Ade Kurnia; Kaslani; Cep Lukman Rohmat (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Cemara Kulon Village, Losarang District, Indramayu Regency is a village located on the north coast of the Java Sea. The name Cemara Kulon itself comes from the name of the Percantilan hamlet which used to be part of the main village, namely Cemara Village, which is now part of the Cantigi District area. The name Cemara comes from the name of a tree which is said to have previously lived in the Cemara Kulon area. The results of assistance in using the QRIS code were carried out 1 month after the assistance was carried out in using the QRIS code, after collecting the data, data reduction techniques or data analysis were carried out which were received by small business actors. before using the QR code and after small business actors use the QR code in the payment process. Before assisting small business actors, they only used cash media or cash payments, which meant that some consumers who were used to using cashless or non-cash media had to make payments in cash, especially in the current era where payment media mostly use transfer media such as m banking, Dana, QRIS code and so on. After providing assistance to small business actors, it is easier to provide services to consumers. Before using the QRIS code, small business actors are confused when someone wants to pay cashless. Consumers are increasing in buying several products from small businesses due to payment via QRIS code. The evaluation carried out after providing training and implementation assistance, there are several things that must be re-evaluated, including the need for scaled or gradual training or assistance for the use of the QRIS code due to the increasingly developing era of digitalization. Small business actors and producers must provide assistance or undergo training on the importance of using the QRIS code so that small business actors are not left behind by the era of digitalization.